OPPORTUNITIES AND CHALLENGES FOR LIVELIHOOD IN HANOI’S URBAN FRINGE DURING THE CURRENT URBANIZATION PROCESS - Yen, Nguyen Thi Hai (IJRDO - Journal of Social Science and Humanities Research, 2019)
Livelihood is the way of living that is selected by the people in accordance with the natural conditions, socio-economic characteristics, ecological environment and is affected by various factors. The urbanization process has brought about many livelihood opportunities for people in Hanoi’s urban fringe. However, it also poses a lot of challenges and shortcomings that require to be solved drastically, such as the employment for laborers after the conversion, social security, etc. On the basis of the study on opportunities as well as challenges for livelihood in Hanoi’s urban fringe during the urbanization process, this article proposes some solutions for sustainable livelihood development in the future.